2020
DOI: 10.5935/1518-0557.20190076
|View full text |Cite
|
Sign up to set email alerts
|

Pre-implantation effects of progesterone administration on ovarian angiogenesis after ovarian stimulation: a histological, hormonal, and molecular analysis

Abstract: Objective: Progesterone (P4) is known to directly affect ovarian tissue angiogenesis. The present study was designed to show how P4 affects ovarian angiogenesis in hormonal, histological, and molecular levels. Methods: Fifteen adult female NMRI mice were divided into three groups: Control Group; Case Group I (ovarian stimulation alone); and Case Group II (ovarian stimulation followed by P4 administration). Blood and ovarian tissue samples were assessed for hormonal, his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Then pseudo pregnancy was performed and after 3.5 days the animals were slaughtered for the study. Concerning the progesterone group (n=5), the process in the induction group was performed followed by daily administration of 1 mg subcutaneous (SC) progesterone for up to 3.5 days ( Narimani et al ., 2020 ). Ethical guidelines for working with laboratory animals were followed and the protocol of this study was approved in the ethics committee of Lorestan University of Medical Sciences under registration number IR.LUMS.REC.1399.300.…”
Section: Methodsmentioning
confidence: 99%
“…Then pseudo pregnancy was performed and after 3.5 days the animals were slaughtered for the study. Concerning the progesterone group (n=5), the process in the induction group was performed followed by daily administration of 1 mg subcutaneous (SC) progesterone for up to 3.5 days ( Narimani et al ., 2020 ). Ethical guidelines for working with laboratory animals were followed and the protocol of this study was approved in the ethics committee of Lorestan University of Medical Sciences under registration number IR.LUMS.REC.1399.300.…”
Section: Methodsmentioning
confidence: 99%
“…Progesterone seems to support its own synthesis by inducing luteal vascularization ( Curry and Nothnick, 1996 ; Pall et al , 2000 ; Stouffer, 2003 ; Peluso et al , 2018 ). Progesterone is known to increase the expression of the vascular endothelial growth factor (VEGF) gene in ovarian tissue in mice ( Narimani et al , 2020 ), granulosa and theca cells in ewes ( Narimani et al , 2020 ), cows ( Shimizu and Miyamoto, 2007 ), and cattle ( Nichols et al , 2019 ). Inhibition of PGRMC1/2 activity is associated with a reduction in the number of vascular endothelial cells within the mouse corpus luteum ( Peluso et al , 2018 ), This effect seems to be independent of VEGF-A but rather related to another novel angiogenesis regulator, lipocalin 2, as its expression in corpus luteum is dependent on the presence of PGRMC1/2.…”
Section: Progesterone-modulated Mechanisms In Luteal Granulosa Cell A...mentioning
confidence: 99%
“…These observations support the vital role of VEGF in progestogen-mediated neovascularization. In addition to in the endometrium, progestogens promote VEGF expression in skin flaps [ 32 ], ovarian tissue [ 33 , 34 ], bovine granulosa cells [ 35 , 36 ], embryonic lung cells [ 37 ], granulomas [ 38 ] and tumor tissues [ 39 , 40 , 41 , 42 ]. However, Keck et al reported an opposite result, founding that P4 has no impact on the proliferation rate of human umbilical vein endothelial cells (HUVECs), a macrovascular cell model used for endothelial studies in vitro [ 43 ].…”
Section: Downstream Factors Involved In Progestogen-mediated Neovascularizationmentioning
confidence: 99%